Genome-Scale Screening, Characterization, and Expression Analysis of Grain Amaranth Small Auxin-Up RNA Gene Family in Response to Drought Stress - Vu, Xuan Duong; Azar, Sahar; Chu, Ha Duc; Le, Quynh Thi Ngoc; Nguyen, Quy Phuong; Nguyen, Thanh Xuan; Nguyen, Dinh Van (HAYATI Journal of Biosciences, 2026)
The Small Auxin-Up RNA (SAUR) gene family represents a class of early auxin-responsive genes that are widely involved in regulating plant cell elongation, tissue differentiation, and environmental adaptation. In this study, we performed a genome-wide analysis of the SAUR gene family in grain amaranth (Amaranthus hypochondriacus), a nutrient-rich pseudocereal. A total of 80 SAUR genes were identified based on the conserved PF02519 domain and were systematically characterized in terms of protein properties, gene structure, and phylogenetic relationships. Most SAUR genes in grain amaranth encode small, basic, and hydrophilic proteins, and gene structure analysis revealed that the majority are intronless. Phylogenetic analysis grouped AhSAURs into ten clades alongside Arabidopsis SAURs. Transcriptomic profiling across seven tissues and drought-treated samples showed that although many SAUR genes had low or no expression, several genes, including AhSAUR76, AhSAUR71, AhSAUR65, AhSAUR54, and AhSAUR73, were highly expressed in a tissue-preferential manner and showed responsiveness to drought. These findings highlight the potential regulatory roles of selected SAUR genes in growth and stress adaptation, offering a valuable resource for future genetic and functional studies aimed at enhancing agronomic traits in grain amaranth.